The Relationship between Lifeguards' Needs and Their Job Satisfaction Based on Maslow's Hierarchy of Needs - Iman Rahimi; Kouros Divsalar; Mohsen Rezvani; Samaneh Sadat Aramoon (Islamic Azad University, 2016)
Introduction: Many studies have been conducted regarding employees' motivation, their job satisfaction and organizational success. The purpose of this study was to investigate the relationship between lifeguards' needs and their job satisfaction based on Maslow's hierarchy of needs. Methods: This field study was a correlational research in which the study sample included all lifeguards who worked in Tehran swimming pools. Based on Krejcie and Morgan table, 306 participants entered the study. Of all distributed questionnaires, 238 questionnaires were returned. In order to collect data, Needs Evaluation Questionnaire (NEQ) and Job Descriptive Index (JDI) were used. For data analysis, Pearson correlation coefficient used (p≤0.05). Results: Findings revealed significant relationship between elementary level needs accommodation and job satisfaction of Lifeguard. It also showed that female lifesaving job satisfaction was in a higher level than male lifesaving job satisfaction. (p≤0.05). Conclusion: It can be concluded that, increasing staff satisfaction in all private organizations in order to achieve efficiency and sport promotion is necessary. Managers of organizations have to try to find the ways to increase lifeguards job satisfaction in order to gain more efficiency.